Perkawinan Beda Agama Ditinjau Dari Aspek Yuridis Hukum Perkawinan di Indonesia - Beridiansyah Beridiansyah (Wajah Hukum, 2023)
Article 1 paragraph (3) of the 1945 Constitution (UUD), the State of Indonesia has declared itself to be a state of law, meaning that in running life and the wheels of government everyone subject to the rules of Indonesian law is obliged to implement and obey them. The law of marriage as regulated in the law of the Republic of Indonesia Number 16 of 2019 concerning amendments to Law Number 1 of 1974 is intended to provide legal certainty in fulfilling the right to continue offspring and be free from the threat of violence and discrimination. This research was conducted to conduct a juridical analysis of marriages conducted by couples of different religions, as a contribution to the author's thoughts on the development of marriage law in Indonesia, the research method used is a normative juridical approach, namely an approach that refers to the applicable laws and regulations, to achieve the objectives of the law itself, namely justice, benefit, and legal certainty.